Factors Influencing Management Accounting Change: A case of Thai Public Universities - Phetphrairin Upping Phetphrairin Upping; Judy Oliver (Indonesian Management and Accounting Research, 2011)
Puzpose - The purpose of this study is to investigate factors influencing management accounting change, with a focus on costing practices, in Thai public universities. Design/metlzodology/appmach - Reports the results of a survey forwarded to the Chief Financial Officers of all 78 Thai public universities. Findings - Findings indicate that the majority of Thai public universities are implementing changes to the costing practices. The main catalysts for change have come f•om both external and internal sources (the govermnent and university management). The Thai government requires public agencies to adapt their management accounting practices in line with New Public Management (NPM) and adopt modern cost accounting practices as used in the private sector. University management also need improved cost information for planning and control purposes to meet the challenges of reduced government funding and increased self management of university affairs. The development of service costs has been important to meet both government and university cost needs. Of the 63 useable responses, 49.21% of the respondents have adopted activity based costing (ABC), however to date only I 6.13% are able to assess the costing change as positive. Lack of appropriate software, difficulty in gathering data on cost drivers and lack of accounting staff understanding of what is required are the main barriers to ABC adoption and successful implementation in Thai public universities. Practical implications - The findings may be helpful to those who are involved in accounting reform in the public sector as it provides further insight into the introduction of NPM practices in a developing counny. -Originality/value - This paper presents a